Chronic E-Cigarette Exposure Alters Human Alveolar Macrophage Morphology and Gene Expression. Issue 3 (14th September 2021) - Davis, Eric S; Ghosh, Arunava; Coakley, Raymond D; Wrennall, Joe A; Lubamba, Bob A; Rowell, Temperance R; Dang, Hong; Pawlak, Erica A; Li, Quefeng; Alexis, Neil E; Ribeiro, Carla M P; Tarran, Robert
Abstract: Introduction: Alveolar macrophages (AMs) are lung-resident immune cells that phagocytose inhaled particles and pathogens, and help coordinate the lung's immune response to infection. Little is known about the impact of chronic e-cigarette use (ie, vaping) on this important pulmonary cell type. Thus, we determined the effect of vaping on AM phenotype and gene expression. Aims and Methods: We recruited never-smokers, smokers, and e-cigarette users (vapers) and performed research bronchoscopies to isolate AMs from bronchoalveolar lavage fluid samples and epithelial cells from bronchial brushings. We then performed morphological analyses and used the Nanostring platform to look for changes in gene expression. Results: AMs obtained from smokers and vapers were phenotypically distinct from those obtained from nonsmokers, and from each other. Immunocytochemistry revealed that vapers AMs had significantly elevated inducible nitric oxide synthase (M1) expression and significantly reduced CD301a (M2) expression compared with nonsmokers or smokers. Vapers' AMs and bronchial epithelia exhibited unique changes in gene expression compared with nonsmokers or smokers. Moreover, vapers' AMs were the most affected of all groups and had 124 genes uniquely downregulated. Gene ontology analysis revealed that vapers and smokers had opposing changes in biological processes. Conclusions: These data indicate that vaping causes unique changes to AMs and bronchial epithelia compared with nonsmokers and smokers which may impact pulmonary host defense. Implications: These data indicate that normal "healthy" vapers have altered AMs and may be at risk of developing abnormal immune responses to inflammatory stimuli.